In Vitro Selective Antibacterial and Antiproliferative Effects of Ethanolic Extracts from Cambodian and Philippine Plants Used in Folk Medicine for Diarrhea Treatment - Kudera, Tomas; Fiserova, Barbora; Korytakova, Marie; Doskocil, Ivo; Salmonova, Hana; Tulin, Edgardo E.; Nguon, Samnang; Bande, Marlito M.; Kokoska, Ladislav (Frontiers in Pharmacology, 2021)
Bacterial diarrhea remains a global health problem, especially in developing tropical countries. Moreover, dysbiosis caused by diarrheagenic bacteria and inappropriate antimicrobial treatment has been associated with intestinal carcinogenesis. Despite the rich tradition of the use of herbs for the treatment of gastrointestinal disorders in Cambodian and Philippine folk medicine, many of them have not yet been systematically studied for their in vitro selective inhibitory effects on intestinal bacteria and cells. In the present study, in vitro inhibitory activities of 35 ethanolic extracts derived from 32 Cambodian and Philippine medicinal plants were determined by broth microdilution method against 12 pathogenic bacteria. Furthermore, cytotoxicity against intestinal cancer cells (Caco-2, HT-29) using thiazolyl blue tetrazolium bromide cytotoxicity assay and safety to six beneficial intestinal bacteria (bifidobacteria and lactobacilli) and intestinal normal cells (FHs 74 Int) were determined for the antimicrobially-active extracts. Selectivity indices (SIs) were calculated among the averages of minimum inhibitory concentrations (MICs), half maximal inhibitory concentrations (IC50), and 80% inhibitory concentrations of proliferation (IC80) for each type of tested agents. The extracts of Artocarpus blancoi (Elmer) Merr. (Moraceae), Ancistrocladus tectorius (Lour.) Merr. (Ancistrocladaceae), and Pentacme siamensis (Miq.) Kurz (Dipterocarpaceae) produced significant growth-inhibitory effects (MICs = 32–512 μg/ml) against intestinal pathogenic bacteria at the concentrations nontoxic to normal intestinal cells (IC80 values >512 μg/ml; SIs = 0.11–0.2). Moreover, the extract of P. siamensis (Miq.) Kurz was relatively safe to beneficial bacteria (MICs ≥512 μg/ml; SI = 0.1), and together with A. blancoi (Elmer) Merr., they selectively inhibited intestinal cancer cells (IC50 values ≥51.98 ± 19.79 μg/ml; SIs = 0.3 and 0.6). Finally, strong selective antiproliferative effect on cancer cells (IC50 values 37.89 ± 2.68 to 130.89 ± 13.99 μg/ml; SIs = 0.5) was exerted by Ehretia microphylla Lam. (Boraginaceae), Lagerstroemia cochinchinensis Pierre ex Gagnep. (Lythraceae), and Melastoma saigonense (Kuntze) Merr. (Melastomataceae) (leaves with flower buds). The results suggest that the above-mentioned species are promising materials for the development of new selective antibacterial and antiproliferative agents for the treatment of infectious diarrhea and associated intestinal cancer diseases. However, further research is needed regarding the isolation and identification of their active constituents.